Is Work Group Social Capital Associated With Sickness Absence? A Study of Workplace Registered Sickness Absence at the Work Group Level - Thomas Clausen; Annette Meng; Vilhem Borg (Elsevier, 2020)
Background: The concept of social capital has its focus on cooperative relations in the workplace. This study investigates the association between social capital and sickness absence among workers in 41 work groups in the Danish dairy industry and examines the possible effects of an intervention on social capital in the workplace on sickness absence. Methods: A sample of 791 dairy workers working in 41 work groups that participated in an intervention study on social capital filled in a questionnaire on four subtypes of social capital, and social capital scores from individual participants were aggregated to the level of work groups. Sickness absence was measured at the level of work groups in company registers as the two-year average percentage of working time lost to sickness absence. Group-level associations between social capital and sickness absence were analyzed using multilevel linear regression analysis. Analyses were adjusted for age, gender, group size, and random effects at the workplace level. Results: We found statistically significant associations between social capital within work groups, social capital in relation to the immediate manager, and social capital toward the workplace as a whole on the one side and sickness absence on the other side. We found no support for any effects of the intervention on sickness absence. Conclusion: The work group level of social capital is associated with the work group level of sickness absence. However, the intervention to enhance group-level social capital had no effect on reducing sickness absence in the intervention group.